PENGARUH SUASANA TOKO, PROMOSI DAN HARGA TERHADAP KEPUASAN PELANGGAN JANJI JIWA DI WILAYAH BEKASI - Rivan Alfandry; Tumpal Janji Raja Sitinjak (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2022)
Coffee consumption has continued to increase over the past few years due to the emergence of new trends in society, especially among young people, where coffee shops become a hangout place and coffee as a drink to accompany gatherings and spend time which is caused by this trend. as an opportunity for entrepreneurs to open a business with coffee-based ingredients so that there are so many coffee shops and the proliferation of coffee franchises in Indonesia. This study examines the effect of Shop Atmosphere, Promotion, Price on Customer Satisfaction Janji Jiwa in Bekasi. The theory used in this research is shop atmosphere, promotion, price and customer satisfaction. There are two types of variables in this study, namely independent which consists of Shop Atmosphere, Promotion and Price, while the dependent variable consists of Customer Satisfaction. The object of this research is the Janji Jiwa. The research method used is multiple linear regression analysis. The data was collected by distributing questionnaires to 100 samples of Janji Jiwa customers in the Bekasi area using simple random sampling technique. The three independent variables, namely shop atmosphere, promotions and prices have a positive and significant effect on customer satisfaction, Janji Jiwa It is recommended that the Janji Jiwa be able to pay attention to customers, especially to provide a comfortable and good shop atmosphere so that customers feel satisfied and it is also recommended that the Soul Promise can provide promotional promotions in the form of cutting prices to attract new customers.